Pengembangan Media Pembelajaran Kirandalam (Kincir Kerajaan Hindu, Budha dan Islam) Untuk Meningkatkan Hasil Belajar Pada Pembelajaran IPAS Kelas IV Sekolah Dasar - Diyah Lisnawati; Firosalia Kristin (DIDAKTIKA, 2024)
Students have difficulty understanding the history of the Hindu, Buddhist, and Islamic kingdoms in science learning because teachers do not use additional media during learning. This study aims to develop media and to determine the level of validity of the "Kirandalam" media and student learning outcomes. This type of research and development R&D research uses the ADDIE model, and the research instruments used in this study are test and non-test techniques. Test techniques can be done by giving tests to obtain students' abilities in cognitive aspects, while non-test techniques are in the form of instruments that will be assessed by media and material experts. The subjects of this study were grade IV students of SD Negeri 1 Bago, with a total of 25 students. "Kirandalam" media received a percentage from media experts of 93.33%, material experts of 88%, and teacher responses of 93.30%. From the three assessors, it was included in the very feasible category so that it can be used for learning media in science learning. The results of the t-test showed that the average score of student learning outcomes before using the media was 63 and the average score after using the media was 81, and based on the paired samples test, the significant value of 0.000 ≤ 0.05 indicated that Ho was rejected and Ha was accepted. Thus, the Kirandalam media can improve the learning outcomes of grade IV students in science learning.